Agile Leadership and its Role in Achieving Organizational Prosperity: An Analytical Study of The Opinions of a Sample of Administrative Leaders in Internet Companies in Sulaymaniyah Governorate - عبدالله, ده رون فريدون; صالح , هه رمي محمد أمين (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
This research aims to analyze the relationship and impact between agile leadership by its dimensions (speed, flexibility, efficiency, cooperation, technology tracking) and organizational prosperity represented by (sustainable competitive advantage, Innovation, intellectual capital, organizational agility) in a number of Internet companies in Sulaymaniyah governorate numbered (9) companies. After reviewing a set of studies and literature, theoretical concepts were written, and build a model and hypotheses based on the dimensions of agile leadership and organizational prosperity, based on the nature of the research and the goals that it seeks to achieve, it has been relied on the descriptive analytical approach. In order to collect the data, a questionnaire was used, and (170) questionnaires were distributed directly as well as electronically via (Google Form) to all members of population represented by the heads of units, administrative departments and supervisors in Internet companies in Sulaymaniyah Governorate, The number is approximately (309) Leaders in all companies according to the companies data while conducting the research. After sorting the received forms directly and checking them, the number of questionnaires which are valid for analysis reached to (125), in addition to (40) questionnaires which are filled electronically, then the total number of valid questionnaires for statistical analysis are (165) forms. Several statistical methods were used, including arbitrators and Cronbach's alpha to verify validity and reliability, factor analysis, simple correlation and structural equation modeling using (SPSS-26) and (AMOS-26). The results showed a positive correlation and effect between the research variables and its dimensions. Based on the results of the research, a number of recommendations were presented related to the need for departments, leaders and supervisors to focus more on adopting and applying the dimensions of agile leadership in order to achieve organizational prosperity for the researched companies.